SOME EFFECTS OF INFORMAL ECONOMY FOR ALBANIAN EMPLOYEES - Muca, Brunilda; Hoxha, Sajmir; Doraci, Galantina (European Scientific Journal, ESJ, 2015)
While Albania transited from a centralized economy into a market economy several concerns which influenced life and behavior of Albanian employees appeared on the scene. One of the most prominent concerns is the appearance of informality in labor market. In Albania, informality is calculated Informality in Albania is calculated to be larger than 50 percent of its official Gross Domestic Product. This paper sheds light on some effects of informal economy in the labor market, mainly on Albanian employees, following a survey conducted in Tirana. It will also offer an approximate calculation of informality, as well as some ideas on raising awareness on effects caused by this phenomenon.